ANALISIS STRATEGI PENYELAMATAN KREDIT MACET MELALUI RESTRUKTURISASI KREDIT PADA BANK BJB CABANG KARAWANG - Iis Rahayu; Dedi Mulyadi; Sungkono Sungkono (JOURNAL SAINS STUDENT RESEARCH, 2024)
One of the main activities of a bank is to disburse money to the public in the form of loans. Although credit disbursement to the public is based on the principles of prudence and sound lending, supported by the goodwill of the lending institution, the possibility of problematic loans still exists. There are several steps that a bank can take to resolve credit issues. One of the efforts made by banks in resolving non-performing loans is through credit restructuring. In this context, the research focuses on three main aspects: (1) The procedure for implementing credit restructuring in resolving non-performing loans at Bank BJB Karawang Branch, (2) The obstacles faced in implementing credit restructuring at Bank BJB Karawang Branch, and (3) Problem-solving strategies to overcome the obstacles in implementing credit restructuring at Bank BJB Karawang Branch. The research method used is a qualitative approach with a case study type. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted using descriptive analysis techniques, while data validity is tested using source triangulation. This research concludes that: (1) The procedure for implementing loan restructuring includes steps after restructuring and monitoring business and financial reports post-restructuring, (2) The bank faces significant obstacles in implementing restructuring measures and is unable to continuously control the commercial and financial affairs of the debtor, and (3) The bank's strategy to address these issues.